2023
DOI: 10.1038/s41598-023-28460-z
|View full text |Cite
|
Sign up to set email alerts
|

Measuring accessibility to public services and infrastructure criticality for disasters risk management

Abstract: Component criticality analysis of infrastructure systems has traditionally focused on physical networks rather than infrastructure services. As an example, a key objective of transport infrastructure is to ensure mobility and resilient access to public services, including for the population, service providers, and associated supply chains. We introduce a new user-centric measure for estimating infrastructure criticality and urban accessibility to critical public services - particularly healthcare facilities wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Accessibility in telemedicine services can be interpreted not from the reach of health services from the patient's distance, but from the ease of accessing health services online for participants as telemedicine users. Accessibility is included in enabling factors include the infrastructure and facilities that are in place to enable or facilitate health behaviour or health actions taken by respondents 17,18 . E-health applications can increase the service accessibility for both customers and health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Accessibility in telemedicine services can be interpreted not from the reach of health services from the patient's distance, but from the ease of accessing health services online for participants as telemedicine users. Accessibility is included in enabling factors include the infrastructure and facilities that are in place to enable or facilitate health behaviour or health actions taken by respondents 17,18 . E-health applications can increase the service accessibility for both customers and health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…The study also underscored the importance of efficient intersection management for overall urban mobility, particularly in disaster-risk scenarios, ensuring swift access to emergency services, and optimizing evacuation routes. Tariverdi et al [50] underscored the critical role of intersection management in ensuring accessibility to essential services, focusing on healthcare facilities. The study identified areas affected by shocks, underserved populations, and changes in accessibility.…”
Section: Dynamic Traffic Management and Adaptive Signal Controlmentioning
confidence: 99%
“…There is a growing recognition that these sectors heavily rely on other supporting infrastructure. Evaluation of social infrastructure interdependencies on a single building level [95], on regional scales [96,97] and on national scales [76] has enabled road-based accessibility studies of health sites and emergency services during climate events [98,99] and network-wide hazard adaptation appraisals [100]. However, modelling frameworks capturing the operational recovery of healthcare and educational services after climate-related disruptions remain understudied.…”
Section: Plos Climatementioning
confidence: 99%